THE EFFECT OF USING PICTURE AS MEDIA ON THE VOCABULARY MASTERY OF JUNIOR HIGH SCHOOL STUDENTS IN TIMOR LESTE BORDER - Fransiska Densiana Luruk; Thresia Trivict (Journal of Language, Literature and Teaching, 2021)
Vocabulary is one of the language components which has an important role in language learning. Without having enough vocabulary someone is impossible to speak or communicate in English. The Purpose of Learning Vocabulary To learn something people have to know the purpose of the things Reviews their learn, in this case the purpose of learning vocabulary is to help the learners Easier in expressing the idea, the research aimed to find out the effect of using picture as teaching media in improving vocabulary at timor leste border.The method in this study is Experimental designwith control and experimental group. The populations in this research used random sampling technique with the number of sample are 42 students; 21 students in control group and 21 students in experimental group. This study was conducted at SMP Satap Negeri Sono Perbatasan Timor Leste, from the eighth grade students in academic year 2017/2018. The instruments that the researcher used arevocabulary test and questionnaire and the research data were collected through a pre-test and post-test and data were analyzed by meand through SPSS 16. The research resultshows revealed that the applying of picture as media in teaching vocabulary could significantly improve their vocabulary and using picture had controibution on students in mastering vvocabulary. Besides, the responses of the experimental group the students of SMP Satap Negeri Sono perbatasan Timor leste have good perception towards the using of picture technique.Therefore it can be concluded that the use of picture media for teaching english especially vocabulary to the students is really effective Keywords: Picture,Teaching vocabulary and Vocabulary Mastery.